Clinico-epidemiological Profile of Women with Non-venereal Vulval Diseases: A Hospital-based Observational Study - Smita Joshi; Shristi Shrestha; Anshumala Joshi (Nepal Journal of Dermatology, Venereology & Leprology)
Intorduction: Vulval disorders can be of venereal and non-venereal etiology. Establishing non-venereal causation of vulval disorder helps in alleviating fears in patients with the condition. These patients are better dealt in a multidisciplinary clinic as patients with these disorders frequently visit dermatologists and gynecologists for the treatment.